Pendekatan Diagnostik Berbasis Manifestasi, Pemeriksaan Klinis dan Tatalaksana Pada Tuberkulosis Paru - Juliana, Risna; Soleha, Tri Umiana; Yunianto, Andi Eka; Ismunandar, Helmi Ismunandar (Medula, 2024)
TB is a disease caused by MTB bacteria where this bacteria is able to attack the lung organs or extrapulmonary organs. The etiology of TB is caused through spit or phlegm from patients whose phlegm contains MTB bacteria. MTB bacteria have a rod shape and are acid-resistant, so they are known as acid-resistant bacteria (AFB). These bacteria do not have spores, so they will easily die if exposed to sunlight. However, this type of bacteria will be difficult to dye because it is acid-resistant, so a special staining method is needed, namely Ziehl Neelsen  staining. When a person coughs, water splashes will spread into the air and will then be inhaled by a healthy person, so the bacteria will enter the lungs and carry out the infection process. Usually, TB disease attacks at a productive age because at that age many people interact socially, making it easier for infectious infections to occur. . In general, the main symptoms are coughing up phlegm, which in some cases can mix with blood, chest pain, and shortness of breath . Confirmation of TB diagnosis can be done by conducting an anamnesis, physical examination, and supporting examination. TB treatment takes 6-12 months for patients who do not experience drug resistance. TB treatment consists of two stages, namely the initial stage and the advanced stage. The initial stage will last for two months, with the type of drug given is a combination of 2 HRZEs (Isoniazid, Rifampicin, Pirazinamid, and Etambutol). The advanced stage of treatment lasted for 4 months, with the drug given in the form of a combination of 4HR (isoniazid and rifampicin).